Tropical Forest and Coral Sea of the Beigua Geopark (Liguria, NW Italy) - Maria Cristina Bonci; Piazza Michele; Briguglio Antonino; Castello Giulia; Caprioglio Cristina; Firpo Marco (Geoconservation Research)
Some of the most interesting paleontological heritage of the Liguria Region is in the Beigua UNESCO Global Geopark, in Savona Province. The Geopark is characterized by high geodiversity and strong tourist traffic, being easily accessible and already having geological and paleontological visitor centers. The geosites of Stella Santa Giustina (SSG) and Maddalena–Ponte Prina (MPP) are remarkable because they show a high diversity of both fossils and fossil-bearing lithofacies and a unique sedimentary sequence that shows different marine and transitional paleoenvironments. The fossils are very well preserved and they illuminate the geological history of the territory, referring in particular to the pre-transgressive and transgressive depositional phases of the Tertiary Piedmont Basin (TPB) on the inner margin of the Ligurian Alps chain during the Oligocene. This sequence spans almost to the end of the Oligocene, which is characterized by one of the major climatic perturbations of the Cenozoic, the Late Oligocene Warming Event (LOWE). The rock exposures reveal how diverse the fauna was just before a major community turnover took place.